Necrotizing amebic colitis in an elder patient: an unexpected autopsy finding - Rodrigues, Maria Aparecida Marchesan [UNESP]; Miamoto, Bruno [UNESP]; Viero, Rosa Marlene [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Necrotizing amebic colitis is an uncommon amebiasis complication associated with high mortality. We present a case of necrotizing amebic colitis in an old patient whose diagnosis was revealed at postmortem examination. An 81-year-old man died at home without medical attention. The postmortem examination revealed ulcers involving the entire colon and intestinal perforation. The ulcers were large, geographic, and necrotizing, extending from the cecum to the rectum. The histological examination disclosed the infectious etiology by showing amebic trophozoites at the base of the ulcers. No extra-intestinal lesions were found. No information about previous episodes of dysentery or travel could be obtained. The potential role of aging or drug-causing immunosuppression and the evolution of chronic and latent intestinal infection to a severe and invasive form of amebiasis is discussed. This case reinforces the value of postmortem examination for diagnosing diseases not clinically identified.
Keywords: Death Cause; Diagnosis; Intestinal Entamoeba histolytica infection